Critical molecular mechanisms that modify bone marrow-mesenchymal stem cell behaviour in advanced breast cancer patients - Borzone, Francisco Raúl (2020)
Most of untreated advanced breast cancer patients (BCP, invasive ductal, stage IIIB) develop osteolytic bone metastasis, due to the existence of a pre-metastatic niche (PMN) that favours extravasa tion, migration, and proliferation of tumor cells. We found that bone marrow (BM) mesenchymal stem cells (MSC) from BCP have lower cloning, proliferation, and osteogenic differentiation capacities than healthy donors (HD) MSC. A conserved pool of functional MSC is essential for preventing the PMN formation.